Cultural influences on dietary choices - Jayasinghe, Sisitha; Byrne, Nuala M.; Hills, Andrew P. (Progress in cardiovascular diseases, 2025)
Food choices and dietary behaviors are inherently complex and influenced by numerous interconnected factors including individual preferences such as taste, meal timing, and social interactions, alongside external elements like affordability, cultural norms, marketing, and policy environments. The physical contexts of food consumption - homes, schools, workplaces, and neighborhoods- further shape these behaviors, as do societal expectations and generational food literacy. Underpinning these dynamics are food systems, which are influenced by health, ethical, and sustainability considerations throughout the food production and consumption continuum. Cultural influences, encompassing traditions, rituals, and shared beliefs, play a pivotal role in shaping dietary practices. Distinctions between “cultural food” and “food culture” illustrate the deep integration of cuisine within identity and daily life. Historical events, globalization, and modernization have reshaped food traditions, leading to the adoption of new eating patterns and the erosion of others. Religion, socioeconomic status, and social networks also critically impact dietary behaviors, while contemporary challenges such as the nutrition transition and fast-food culture contribute to rising chronic disease burdens. Addressing these issues requires culturally tailored interventions and a focus on food environments, integrating modern tools like social media to promote healthier, community-oriented behaviors while recognizing the social and emotional roles of food. [Display omitted]